Acute Miliary Tuberculosis Of Skin - A Case Report And Review Of Literature - Raut W .K; Sawaitu V. K; Bobhate S . K; Fule R .P; Salodkar A . D (Wolters Kluwer Medknow Publications, 2002)
Acute military tuberculosis of skin is a rare manifestation of tuberculosis. A 7 month old female presented with multiple subcutaneous nodules all over the body. Fine needle aspiration cytology and biopsy from the nodule showed tuberculous lesion with demonstration of acid-fast bacilli (AFB). A typical presentation of cutaneous tuberculosis in HIV era and its diagnosis by AFB stain is stressed.